Molecular genetic markers as a basis for personalized medicine - Pavlović Sonja; Zukić Branka; Stojiljković-Petrović Maja (Journal of Medical Biochemistry, 2014)
Nowadays, genetics and genomics are fully integrated into medical practice. Personalized medicine, also called genome-based medicine, uses the knowledge of the genetic basis of disease to individualize treatment for each patient. A number of genetic variants, molecular genetic markers, are already in use in medical practice for the diagnosis, prognosis and follow-up of diseases (monogenic hereditary disorders, fusion genes and rearrangements in pediatric and adult leukemia) and presymptomatic risk assessment (BRCA 1/2 for breast cancer). Additionally, the application of pharmacogenomics in clinical practice has significantly contributed to the individualization of therapy in accordance with the patient's genotype and gene expression profile. Genetic testing for several pharmacogenomic markers (TPMT, UGT1A1, CYP2C9, VKORC1) is mandatory or recommended prior to the initiation of therapy. The most important achievement of genome-based medicine is molecular-targeted therapy, tailored to the genetic profile of a disease. Testing for gene variants in cancer (BCR-ABL, PML/RARa, RAS, BCL-2) is part of the recommended evaluation for different cancers, in order to achieve better management of the disease. The ultimate goal of medical science is to develop gene therapy which will fight or prevent a disease by targeting the disease-causing genetic defect. Gene therapy technology is rapidly developing, and has already been used with success. Although medicine has always been essentially "personal" to each patient, personalized medicine today uses modern technology and knowledge in the field of molecular genetics and genomics, enabling a level of personalization which leads to significant improvement in health care.